What are the factors that enhance metacognitive skills in nursing students? A systematic review - Shadi Asadzandi; Rita Mojtahedzadeh; Aeen Mohammadi (Wolters Kluwer Medknow Publications, 2022)
Background: Metacognitive skills have an important role in training efficient learners and competent clinicians in health professions education. The aim of this systematized review was to determine the factors enhancing metacognitive skills in nursing students. Materials and Methods: For data collection, we searched the databases of PubMed, Ovid, Cochrane, Scopus, Web of Science, ProQuest, Springer, EMBASE, Science Direct, PsycInfo, Nursing and Allied Health, and ERIC up to the end of March 2019, using the study key words. We used PRISMA flowchart diagram for reporting the results of the study. Peer-reviewed articles in English, addressing factors enhancing metacognition in nursing students, were included in our review. The Critical Appraisal Skills Program (CASP) checklist was used for assessing the quality of the included studies. Results: Out of 2355 studies, 16 were included for the review. Several factors, namely "specific curricular activities," "self-regulated e-learning modules," "e-portfolio," "cognitive apprenticeship," "specific teaching techniques for classroom and experiential settings," "metacognitive wrappers," "problem-based learning," "blended learning," "grit," and "clinical log," enhancing metacognition in nursing students, were extracted. Conclusions: The findings of our study can contribute to planning for improvement of learners' metacognitive skills. However, there is a need for future research on determining further factors influencing nursing students' metacognitive skills.